ABDOMINAL SACROHYSTEROPEXY-A CONSERVATIVE SURGICAL TREATMENT OF UTERINE PROLAPSE - Khursheed, Farkhunda; Das, Chandra Madhu; Ghouri, Ambreen (Journal of Ayub Medical College Abbottabad, 2013)
Background: The traditional surgical treatment of utero-vaginal prolapse is vaginal hysterectomy. In recent years, the procedure of sacral hysteronpexy is gaining popularity. This study was conducted to determine the frequency of uterine prolapse in young women and to analyze the results of abdominal sacrohysteropexy. Methods: This descriptive case series was conducted in department of Gynaecology and obstetrics Unit-II, Liaquat University of Medical and Health Sciences form October 2008 to October 2011. All those women admitted during the study period with uterine prolapse and requiring uterine conservation surgery were included in the study. After evaluation and pre- operative assessment, abdominal sacrohysteropexy was performed. Results of surgery were analyzed in terms of duration of surgery, intra-operative and post-operative complications, need for blood transfusion during surgery and duration of hospital stay. After discharge they were followed for a period of 6 months. Results: A total of 210 cases of uterine prolapse were admitted during the study period. Out of these, abdominal sacrohysteropexy was performed in 33 cases (15.71%). In these 33 cases, 4 (12.12%) were unmarried and 29 (87.87%) were married. In 29 married women, 10 (34.48%) were nulli-para, 12 (41.37%) were para 1 or 2 and 7 (24.13%) were para 3-5. Regarding the age of these women, 7 (21.21%) were less than 25 years, 16 (48.48%) were between 25-34 years and 10 (30.30%) were between 35-45 years. Duration of surgery was between 30-45 minutes in most of the cases (96.96%). Blood loss during surgery was <100 ml, only in 1 case it was between 100-300 ml, where one unit of blood was transfused. Regarding postoperative complications only 1 case had wound sepsis. Most of the cases (93.93%) were discharged at 3rd or 4th postoperative day. No complaints were found during follow up period of 6 months. Conclusion: Abdominal sacrohysteropexy can be considered as a safe and effective treatment of uterine prolapse in young and in those women who desire to retain the uterus. Keywords: Uterine prolapse, frequency, abdominal sacrohysteropexy, young women